FACTORS OF LACK OF READING ABILITY AMONG SEVERELY IMPROVED STUDENTS IN CLASS V OF PAYA KULBI STATE PRIMARY SCHOOL - Katrunnada Katrunnada; Siti Mayang Sari (Sensei International Journal of Education and Linguistic, 2024)
This research method uses descriptive qualitative which focuses on the natural conditions of objects for students (Sf). The aim of this research is to determine the factors that cause a lack of reading ability (Sf). Based on what happened in the field, there was a problem with the reading ability of one of the students in class V of Paya Kulbi State Elementary School, namely (Sf), who was known to have a mild mental retardation as seen from his learning ability and reading difficulties. Reading ability is the student's ability to recognize letters and words, then connect them with sounds and understand the meaning of what is read and this cannot be done by (Sf). Mental retardation is an intelligence ability below average so that students who experience mental retardation have great difficulty understanding learning. The results of research using observations and interviews found that the factors causing the lack of reading ability in (Sf) consisted of endogenous and exogenous factors, where from endogenous, namely there were mentally retarded hereditary cells from the mother, and from exogenous, namely students did not receive support from their parents to hone their abilities. learn it.